Expression of hepatitis B virus X protein in HBV-infected human livers and hepatocellular carcinomas - Su, Qin; Schröder, Claus Hobe; Hofmann, Walter J.; Otto, Gerd; Pichlmayr, Rudolf; Bannasch, Peter (Hepatology, 1998)
Transactivation of cellular genes and functional inactivation of p53 by the hepatitis B virus (HBV) X gene-encoded protein (HBx) are proposed as alternative mechanisms for induction of hepatocellular carcinomas (HCCs) in chronic HBV infection. Using an immunohistochemical approach, we studied the expression of HBx in 39 explanted livers with HBV-associated disease. Because the data reported previously have been inconsistent, possibly due to the application of different antibodies, we compared results with 5 polyclonal and 6 monoclonal anti-HBx antibodies from five laboratories. Ten of the 11 antibodies reacted with recombinant HBx by Western blotting, but only 1 polyclonal and 2 monoclonal antibodies reacted specifically with HBx in tissue, and were thus suitable for immunohistochemistry. Three other polyclonal antibodies reacted with tissue components in addition to HBx. One polyclonal and 4 monoclonal antibodies did not recognize the HBx in the tissue. HBx was demonstrated in 16 of 30 (53.3%) cirrhotic livers and 10 of 18 (58.8%) HCCs by all specific antibodies. The expression of HBx, among three HBV antigens examined, was found to be preferentially maintained in HCC and the surrounding liver parenchyma, including focal or nodular preneoplastic lesions. However, the immunoreactivity was always limited to the cytoplasm of a small number of parenchymal and neoplastic cells. The role of X gene expression in HBV-associated human hepatocarcinogenesis remains to be established.
Elektronische Reproduktion der Druck-Ausgabe 30. Dezember 2003
Gesehen am 04.11.2025